Speech and language therapists’ decision-making process: exploring factors behind intervention decisions for children with developmental language disorder in Turkey - Durgungoz, Fatma Canan (2019)
Introduction and Aim: This is a qualitative study which explores how speech and language therapists (SLTs) make decisions. The purpose is to investigate the factors which influence SLTs’ decision-making processes when they engage with children with developmental language disorder (DLD). There is a lack of research and evidence about how SLTs come to a decision to administer a particular therapy session. SLTs’ therapy practices might vary for similar cases and such diverse practices might stem from SLTs’ clinical reasoning processes.